2018
DOI: 10.4103/apos.apos_20_18
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Primary Stability of Mini Implants Using Resonance Frequency Analysis

Abstract: Introduction In the last decade, anchorage control with mini-implants has gained enormous credibility in maintaining orthodontic anchorage. Resonance frequency analysis (RFA) has proven to be an adequate method to measure the stability of these mini-implants because of its non-invasiveness and contactless measurement method. Materials and Method Tomas and S.K surgical mini-implants were tested. For this purpose custom fabricated attachment was fabricated to attach the smart peg on orthodontic mini-implant he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
3
3
2
Order By: Relevance
“…However, the results of this study are in contrast with study done by Singh AK et al, 5 Song et al 21 and Neinkemper et al 22 They concluded that primary stability of mini implants is not affected by changes in length of mini implant. These differences in results found may be due to variation in brands of implants used, 5 or changes in diameter along with length of implants studied.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the results of this study are in contrast with study done by Singh AK et al, 5 Song et al 21 and Neinkemper et al 22 They concluded that primary stability of mini implants is not affected by changes in length of mini implant. These differences in results found may be due to variation in brands of implants used, 5 or changes in diameter along with length of implants studied.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results of this study are in contrast with study done by Singh AK et al, 5 Song et al 21 and Neinkemper et al 22 They concluded that primary stability of mini implants is not affected by changes in length of mini implant. These differences in results found may be due to variation in brands of implants used, 5 or changes in diameter along with length of implants studied. 21 In this study, we selected constant diameter and brand for both the groups to prevent any changes in surface morphology, only factor that was altered was the length of the implants studied.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the long mini-implant can fracture during insertion because it needed a higher insertion torque 11 . Contrary to the present study were the results of Singh AK et al 20 and Ohali HA 21 . They stated that an increase in length did not affect the stability of mini-implant.…”
Section: Implant Angulationscontrasting
confidence: 99%